Affirmative Action in the Educational Sector: A Discriminative Practice or for Promoting Peaceful Living? - Imoh, Colins (In Factis Pax: Journal of Peace Education and Social Justice, 2024)
The article discusses the admission process for Unity schools in Nigeria, which uses affirmative action to ensure the representation of students from all regions of the country. The policy promotes fairness, equity, and justice in education by compensating disadvantaged groups without equal access to opportunities, rights, and ‘social bases of self-respect’. Affirmative action removes obstacles that prevent individuals from pursuing their goals and ensures that all parts of the country are represented. They might not be the most intelligent students, but they are the best in their region. The evidence shows that affirmative action is not discriminatory but relatively justifiable as a temporary measure to reduce the educational imbalance between the northern and southern parts of the country. With limited school spaces and numerous applicants, the admission policy prioritizes diversity, equity, and unity. Without this policy, the schools would be dominated by students from the south of Nigeria, which could lead to conflict and a lack of positive peace. Educational achievement discrepancies, such as disparities in access to quality education, resources, and opportunities, have the potential to breed distrust and conflict within communities.